Empowerment of healthcare cadres on Stimulation of Early Detection and Intervention of Growth and Development - Amellia Mardhika; Joko Susanto; Eny Qurniyawati; Anestasia Pangestu Mei Tyas (University of Merdeka Malang, 2022)
Children’s physical, mental, social, and emotional growth and development are influenced by nutrition, health, and education. This factor can be identified by conducting early screening to see growth and development deviations in children. So interventions can be carried out as early as possible as an initial corrective action or deviations do not become more severe, and referrals are made as early as possible according to indications. Data on the coverage of health services for children under five in Lamongan Regency was 1,738 (92.3%) of 1,882 toddlers in 2019, while data in Pucuk Subdistrict contained 36 under-fives with less nutrition than 2,591 under-fives who were weighed aged 0-59 months (1.4%), 29 short toddlers out of 2,588. toddlers 0-59 months height measured (1.1%), and 68 underweight toddlers (2.6%). The target of the activity is to increase the knowledge and skills of cadres in carrying out the Stimulation of Early Detection and Intervention of Growth and Development (SDIDTK). The method is carried out in three stages, the socialization stage in the form of health education and training of cadres, the work stage in the form of mentoring during Integrated Healthcare Center (Posyandu), and the evaluation and recommendation stage. Cadres are very enthusiastic in following the material and are active during mentoring. The increase in knowledge was seen in the pre-test and post-test scores.